If

2X + 3Y = 12 , what is

X ?

1)

X = 6 - (\frac{3}{2})Y2)

Y = 4 - (\frac{3}{2})X Why is statement 1 not sufficient?

Can I not find the value of Y and substitute in

2X + 3Y = 12. I did this, please tell me what mistake I am making

2X = 12-3YFrom Statement 1

X = 6 - (\frac{3}{2})YWhich can be simplified to

X = (\frac{9}{2})YTherefore,

Y = (\frac{2}{9})XNow if i can substitute this Y in

2X = 12-3Y2X = 12-\frac{6}{9}X2X = 12-\frac{2}{3}X2X+\frac{2}{3}X = 12\frac{8X}{3} = 128X = 36X = \frac{36}{8} _________________

My First Blog on my GMAT Journey

Arise, Awake and Stop not till the goal is reached